Literatura eletrônica: análise e sugestão de atividades com as obras literárias digitais no ensino fundamental II - Chimenes, Edna Gamboa (2020)
In a context in which technology is increasingly present in activities and social configuration, textual practice is being pressured to be part of this context, as it is an area where new readers need encouragement and knowledge related to the construction of knowledge or to the understanding of the work. There is also the need for a reflection on the definitions of the types of readers, presented by Santaella (2004, 2013), to assist in the understanding of different languages and interaction between the elements of electronic texts. Thus, this work seeks to extract the main characteristics of digital literature, from a qualitative analysis of an interpretative nature, using as object eight digital literary works, from the Digital Literature website, organized by Marcelo Spalding. The objective is to analyze the (re) configuration of the literary language, observing, in the eight selected digital works (A study in red, Enigma, Terminal, The game of the poet cat, Seasonal Labyrinths, Hyperlendas Mato-Grossenses, Me in command and Ciberpoesia), the aesthetic construction used, suggesting a reading practice, directed to the students of Elementary School II, that uses these works, from the Rhizomatic Perspective thought by Sílvio Gallo (2008). According to Deleuze and Guattari (2004, p. 15), they point out that “multiplicities are rhizomatic and denounce arborescent pseudomultiplicities. Therefore, there is no unity that serves as a pivot in the object or that divides in the subject”. The theoretical basis is based on the presentation and consideration of the relationship between literature and technology, in the comparison and analysis of the digital and the digitized, in addition to the definition and possibilities of intermidiality, reaching the tools that effectively characterize the digital literature, from the concepts presented by Lévy (1998), Hayles (2009), Santaella (2004, 2013), Gallo (2008), among others. The study considers that different works make use of certain elements as composers of the construction of the plot, expanding and bringing other elements for the reading and interpretation of the text, according to the objective that is outlined for each one of them.